2009
DOI: 10.1126/science.1167595
|View full text |Cite
|
Sign up to set email alerts
|

Subducting Slab Ultra-Slow Velocity Layer Coincident with Silent Earthquakes in Southern Mexico

Abstract: Seismic mapping suggests that silent earthquakes may be related to an ultralow velocity layer on top of a subducting slab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
245
2
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(267 citation statements)
references
References 25 publications
19
245
2
1
Order By: Relevance
“…Low frequency earthquakes (LFEs) have also been observed in coincidence with the slow slip and tremor in subduction zones, with focal mechanism and location consistent with interplate slip (Shelly et al 2006(Shelly et al , 2007. Recent seismic and numerical modeling results point to the contribution of elevated fluid pressure near the plate interface (Audet et al, 2009;Kodaira et al, 2004;Liu and Rice, 2007;Song et al, 2009). These findings are consistent with thermo-…”
Section: Accepted M Manuscriptsupporting
confidence: 74%
See 1 more Smart Citation
“…Low frequency earthquakes (LFEs) have also been observed in coincidence with the slow slip and tremor in subduction zones, with focal mechanism and location consistent with interplate slip (Shelly et al 2006(Shelly et al , 2007. Recent seismic and numerical modeling results point to the contribution of elevated fluid pressure near the plate interface (Audet et al, 2009;Kodaira et al, 2004;Liu and Rice, 2007;Song et al, 2009). These findings are consistent with thermo-…”
Section: Accepted M Manuscriptsupporting
confidence: 74%
“…The low Vs layer (denoted as "ultra-slow velocity layer" (USL) by Song et al, 2009) atop the subducted Cocos crust appears to be in direct contact with overlying continental crust material (Kim et al, 2010(Kim et al, , 2012Perez-Campos et al, 2008), and the seismic velocity variations along the plate interface outline the seaward (updip) and landward (downdip) limits of the seismogenic zone (Song and Kim, 2012). The updip region near the Pacific coast shows a smaller…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Main cities along the array are marked with red circles. a low permeability layer directly above the interface in the continental lower crust (Song et al 2009;Kim et al 2010), and that it might be composed of mechanically weak hydrated minerals, such as talc (Kim et al 2010(Kim et al , 2013. The latter is in accordance with numerical experiments of Manea et al (2013), which model the LVL as a remnant of the mantle wedge that experienced significant serpentinization since the onset of flat subduction.…”
supporting
confidence: 68%
“…Kim et al (2010) performed an inversion using the amplitudes of the converted teleseismic phases and obtained high Vp/Vs of $ 2:0 within the flat upper oceanic crust of the Cocos plate beneath central Mexico. Furthermore, both finite-difference modeling of the RFs (Kim et al, 2010) and modeling local converted S-to-P phases and teleseismic underside reflections (Song et al, 2009) for the shallow-to-flat slab region ( $ 20245 km depth) suggested anomalously low S wave velocity of 2.4-3.4 km/s for 200 km from the Pacific coast.…”
Section: Introductionmentioning
confidence: 99%
“…In central Mexico, significant reduction in S wave velocity by more than 20% (Song et al, 2009) at the shallow-to-flat transition of the top interface of the Cocos plate ( $ 20245 km depth) are difficult to explain simply by velocity difference predicted for plausible subducted oceanic crust lithologies such as lawsonite blueschist and epidote blueschist (Currie et al, 2002), which is only less than 7% (Hacker et al, 2003a). In comparison to previously reported values for central Mexico subduction zone, the Vp/Vs ratios (or Poisson's ratios) shown in Audet et al (2009) and Peacock et al (2011) for Cascadia subduction zone are quite extreme, and both Audet et al (2009) and Peacock et al (2011) argued that such high estimates cannot be due to the presence of hydrous minerals alone but are due to free-water at high porepressure.…”
Section: Introductionmentioning
confidence: 99%